Android-Based E-Module Development on Network Operating System Material: Pengembangan E-Modul Berbasis Android pada Materi Sistem Operasi Jaringan - Imamah, Nur; Hasanah, Fitria Nur (Indonesian Journal of Education Methods Development, 2023)
The purpose of this study was to produce an android-based e-module learning product on the material of the class XI TKJ network operating system and to determine the feasibility of an android-based e-module. This type of research uses R & D Research and Development with the ADDIE research and development model consisting of alaysis (analysis), design (design), development (development), implementation (Implementation) and evaluation (evaluation) stages. class XII TKJ SMK Muhammadiyah 1 Taman, the implementation is in class XI TKJ students. After the development process, media experts and material experts were validated as well as small-scale trials consisting of 5 students. So it can be concluded that android-based e-modules are suitable for use as teaching materials with the results of media expert validation of 86.6% in the very feasible category, the results of material expert validation by 85% in the very feasible category and small-scale trials getting an average percentage by 83.26%.